A Perspective on Rational Designs of a Hemagglutinin Based Universal Influenza Vaccine - D. Van, Thanh; Tran, Nhut; Le, Ly; Eisenhaber, Frank (Current Pharmaceutical Design, 2016)
Background: The influenza virus is one of the most critical threats to public health with major economic impact. Though annual influenza vaccination is currently the most effective prevention strategy against flu epidemics and pandemics, the mutational evolution of the influenza virus tends to reduce the effectiveness of strain-specific vaccines. Methods: For past decades, a broad spectrum of potentially universal influenza vaccines has been thoroughly investigated to suppress different strains and subtypes of influenza virus concomitantly. Universal influenza vaccines were attempted to be designed to target conserved regions of surface receptors to provide the necessary preventive strategy against new influenza outbreaks. Conclusion: Notably, the influenza hemagglutinin (HA) receptor has evolutionary conserved domains that can serve as basis for the rational design of a universal influenza vaccine. In this review, we examine recent studies on HA-based universal influenza vaccines and address their molecular mechanism.
Keywords: hemagglutinin (HA)